Acuerdos de integración en Colombia ¿Y el comportamiento de los agentes? (2015)
This article shows a review of academicals documents about the agreements of economic integration signed by Colombia, it with the objective to identify new criterions which could improve next national agreements. The review includes a look at some frameworks about the principles of economic integration and the studies of integration processes in Latin American, which make evident that the economic integration is a good tool to generate development process. However, the examined frameworks are not enough on all literature about analysis of economic integration, because it have limited to contrast the agreements results, leaving aside other possible fields of study.